Comparative Assessment of The Strategies of Leading Global Maritime Container Operators Towards the Challenges of the 2020-2022 Crisis - Andrzej S. GRZELAKOWSKI (Communications of International Proceedings, 2023)
Covid-19 pandemic crisis hit seriously the entire mega-logistics sector, particularly affecting the global container shipping one. However, due to its favorable market conditions, as well as thanks to adopted at that time by container shipping carriers short- and medium-term strategies, focused on survival through development, they became ultimately the beneficiary of that deep economic crisis. The subject of the research covers the issues concerning mid and long-term strategies of the global container operators used in the years 2020-2022, treated as main guidelines and indications for achieving their goals in an era of massive supply chain disruptions. The main aim of the study is to assess these strategies in terms of their effectiveness and compatibility towards the challenges they faced and determine the reasons for strategy changes during the crisis period 2020-2022. This study aims to contribute to understanding the strategic decisions of global container shipping carriers and how they respond to global market and regulatory changes. There were applied such research methods and techniques as: desk research and data exploration as well the factors analysis (FA), market analysis (MA) and SWAT analysis. Moreover, there were conducted interviews with few representatives of the global leading container shipping operators. The obtained research findings indicate that the applied global maritime container carriers’ strategies during the pandemic crisis were headed to overcoming disruptions in the global supply chains, keeping on operational stability at the same time, as well as maintaining, and further on increasing, maximal revenues in the most prosperous for the operators period of the market changes. However, it was achieved essentially at the expense of shippers and forwarders.
Keywords: container shipping operators’ strategies; market and regulatory challenges; strategies towards market reality; shipping green transformation